Discretionary justice : pardon and parole in New York from the revolution to the Depression - Strange, Carolyn, 1959- (New York : New York University Press, 2017)
The pardon is an act of mercy, tied to the divine right of kings. Why did New York retain this mode of discretionary justice after the Revolution? And how did the advent of the penitentiary and the introduction of parole transform governors' use of their prerogative? This text answers these questions by mining previously unexplored evidence held in official pardon registers, clemency case files, reports of prisoner aid associations, and parole hearing records.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 31, 2017).
Keywords: Pardon -- New York (State) -- History; Pardon -- New York (State) -- History -- Sources; Parole -- New York (State) -- History; Parole -- New York (State) -- History -- Sources; True Crime; Social services & welfare, criminology